Fast diffusion of silver in TiO2 nanotube arrays - Zhang, Wanggang; Liu, Yiming; Zhou, Diaoyu; Wang, Hui; Liang, Wei; Yang, Fuqian (Beilstein Journal of Nanotechnology, 2016)
Using magnetron sputtering and heat treatment, Ag@TiO2 nanotubes are prepared. The effects of heat-treatment temperature and heating time on the evolution of Ag nanofilms on the surface of TiO2 nanotubes and microstructure of Ag nanofilms are investigated by X-ray diffraction, field emission scanning electron microscopy, and transmission electron microscopy. Ag atoms migrate mainly on the outmost surface of the TiO2 nanotubes, and fast diffusion of Ag atoms is observed. The diffusivity for the diffusion of Ag atoms on the outmost surface of the TiO2 nanotubes at 400 °C is 6.87 × 10−18 m2/s, which is three orders of magnitude larger than the diffusivities for the diffusion of Ag through amorphous TiO2 films. The activation energy for the diffusion of Ag atoms on the outmost surface of the TiO2 nanotubes in the temperature range of 300 to 500 °C is 157 kJ/mol, which is less than that for the lattice diffusion of Ag and larger than that for the grain boundary diffusion. The diffusion of Ag atoms leads to the formation of Ag nanocrystals on the outmost surface of TiO2 nanotubes. Probably there are hardly any Ag nanocrystals formed inside the TiO2 nanotubes through the migration of Ag.
Keywords: activation energy; fast diffusion; magnetron sputtering; silver; TiO2 nanotube